WiFiCar: movement control via gpio on linksys WRT54GL / Mukhriz Zakaria - Zakaria, Mukhriz (2007)
This paper consists of the development, implementation of data capturing on a wireless device. The chosen wireless device, wireless router Linksys WRT54GL was remodeled with open source base and extra wiring configurations to add features and take advantage of its processing capabilities. An application which is, WiFiCar is chosen to demonstrate the functionality of the newly found platform with the idea of manipulating the concept of General Purpose Input Output (GPIO). The main technology drive is IEEE 802.11. The development being carried out will examine the functionality of the platform and its future possibilities. Procedures included to materialize this idea are by developing a working model, testing and analyzing in order to evaluate the whole concept. The expected outcome of this paper is extending the capabilities of wireless environment replacing traditional wired environment, and opening to new possibilities to wide use of applications not available before due to the limitations imposed by the default configurations and operating system.